Reproducibility of Illumina platform deep sequencing errors allows accurate determination of DNA barcodes in cells. Issue 1 (December 2016) - Beltman, Joost; Urbanus, Jos; Velds, Arno; van Rooij, Nienke; Rohr, Jan; Naik, Shalin; Schumacher, Ton
Abstract Background Next generation sequencing (NGS) of amplified DNA is a powerful tool to describe genetic heterogeneity within cell populations that can both be used to investigate the clonal structure of cell populations and to perform genetic lineage tracing. For applications in which both abundant and rare sequences are biologically relevant, the relatively high error rate of NGS techniques complicates data analysis, as it is difficult to distinguish rare true sequences from spurious sequences that are generated by PCR or sequencing errors. This issue, for instance, applies to cellular barcoding strategies that aim to follow the amount and type of offspring of single cells, by supplying these with unique heritable DNA tags. Results Here, we use genetic barcoding data from the Illumina HiSeq platform to show that straightforward read threshold-based filtering of data is typically insufficient to filter out spurious barcodes. Importantly, we demonstrate that specific sequencing errors occur at an approximately constant rate across different samples that are sequenced in parallel. We exploit this observation by developing a novel approach to filter out spurious sequences. Conclusions Application of our new method demonstrates its value in the identification of true sequences amongst spurious sequences in biological data sets.